O imaginário místico e cultural da cidade da Bahia : uma leitura de Bahia de Todos os Santos: guia de ruas e mistérios, de Jorge Amado - Ferreira, Tatiane Almeida (2013)
This work aims at analyzing the dialogic relationship between literature and its illustration in order to show the creation of imaginary formed on the black – mixed people, the traditions, the mystique surrounding the "City of Bahia " with its syncretism religious, faith and popular festivals. This discursive intersection gives rise to other forms of reading, interpreting, serving for the understanding of the unique aspects about the varied universe mythical- religious and cultural place. We take as an example the illustrated edition of Bahia de Todos os Santos: street guides and mysteries, Jorge Amado, 1977 edition, featuring the designs of Carlos Bastos. The approach is interdisciplinary because the intent of the writer was to build an artistic, historical- cultural and human panel of Bahian metropolis, so many sources of knowledge, artistic forms were used in order to understand an imaginary, gestated in reality and invention. The city is widely known as the writer proposes to show it to an imaginary tourist, that it may come to know it in its concreteness. For these reasons, the text seems to set up a tour guide, however its operatic quality, interspersed with the mystery, let’s find its fictional quality. Moreover, the work is a cultural-historical testimony, to discuss issues of the past and who are pressing for the decade in which the guide has been updated since the city of Salvador urbanized throughout the twentieth century and grew up with her problems social and economic character.